AN ANALYSIS OF VOCATIONAL HIGH SCHOOL STUDENTS’ AWARENESS OF PROFESSIONAL ATTITUDES DURING INDUSTRIAL INTERNSHIP - Dadang Solihat; Trisye Fujianti; Digna Syamsiar (FKIP & Sekolah Pascasarjana Universitas Kuningan, 2025)
This study investigates vocational high school students’ awareness of professional attitudes during industrial internships, focusing on how such awareness contributes to the formation of vocational work ethic. Employing a qualitative descriptive research design within an interpretivist paradigm, the study explores students’ lived experiences and reflective processes in authentic workplace settings. Data were collected through semi-structured interviews, reflective journals, and document analysis involving vocational high school students who had completed or were undertaking industrial internships across various industry sectors. The data were analyzed thematically to identify patterns of awareness related to professional attitudes. The findings reveal five key dimensions of awareness developed during internships: responsibility and work commitment, discipline through workplace norms, ethical awareness and professional conduct, communication awareness, and professional identity formation. The results indicate that students’ awareness of professional attitudes emerged progressively through experiential engagement, feedback, and reflective encounters with workplace demands. Awareness functioned as a mediating process that transformed external work experiences into internalized professional values. This study contributes to vocational education research by foregrounding students’ internal learning processes and conceptualizing vocational work ethic as an outcome of awareness-based learning rather than mere behavioral compliance. The findings suggest that industrial internships should be designed as reflective learning spaces supported by intentional pedagogical strategies to strengthen students’ professional attitude development and long-term employability.